Improvement of Student Learning Outcomes Using E-Worksheets Assisted Live Worksheets on Basic Chemistry Laws Material - Arifianti, Dwi; Yanuardani, Ayu; Khasanah, Maulidia Uswatun; Kusumaningrum, Yesika Dewi; Ayunin, Khurota; Azizah, Utiya; Asih, Dian; Rahadityo, Purwo (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
This study investigates the improvement of student learning outcomes using e-worksheet media with Live Worksheets. Conducted as Classroom Action Research (CAR), it involved 38 students from class X-7 at SMA Negeri 18 Surabaya. Data collection included observation techniques and learning outcome tests aimed at assessing teacher and student activities. The observation data were analyzed using a percentage formula for relevant activities over two meetings. Learning outcome tests measured improvements after cycles I and II, analyzed for the percentage of classical completeness in learning outcomes. Results indicated that teacher activity increased from 91% in cycle I to 100% in cycle II, while student activity rose from 79% to 89%, which falls into the very practical category. Additionally, learning outcomes improved significantly, increasing from 50% before the intervention to 79% in cycle I and 89% in cycle II, which is ≥75%. These findings demonstrate the effectiveness of e-worksheet media in improving educational engagement and achievement. The study concludes that technology-based learning innovations can effectively address educational challenges and recommends further development of interactive learning tools across various subjects and educational levels.